IMPLEMENTATION OF DOUBLE EXPONENTIAL SMOOTHING METHOD IN WORLD GOLD PRICE PREDICTION APPLICATION - Hizamrul Jaen; Cindy Rahayu (PT. Radja Intercontinental Publishing, 2023)
The constantly changing price of gold in the world can worry gold investors, so accurate and fast data is needed to respond to these changes. The role of technology and appropriate procedures is crucial in addressing these challenges. This research will discuss the Prediction of World Gold Prices as a Support for Gold Stock Investment Decisions Utilizing Time-Varying Prediction Algorithms such as Double Exponential Smoothing, which utilizes historical data as a reference in the prediction calculation. The historical data sample used in this study ranges from the beginning of September 2019 to the end of October 2019. From this research, it is expected to test the Double Exponential Smoothing method in predicting future world gold prices.